The efficacy of different types of cerebral embolic protection device during transcatheter aortic valve implantation: a meta-analysis - Wang, Chao; Han, Jingjun; Lu, Liuyi; Qiu, Junxiong; Fu, Yuan; Zheng, Junmeng (Frontiers in Cardiovascular Medicine, 2024)
Aims Perioperative stroke remains a devastating complication after transcatheter aortic valve implantation (TAVI), and using a cerebral embolic protection device (CEPD) during TAVI may reduce the occurrence of stroke according to some studies. Therefore, we conducted this meta-analysis to determine whether CEPD should be routinely used during TAVI. Methods and results The inclusion criteria for this study were randomized controlled trials (RCTs) that examined the outcome of stroke with or without CEPD during TAVI, with a minimum follow-up period of 30 days. The primary endpoint was the occurrence of stroke (including both cerebrovascular accidents and death due to cerebrovascular accidents). The risk of stroke was lower in the CEPD group: RR 0.68, 95% CI 0.49–0.96, p = 0.03, I2 = 0%. A subgroup analysis was conducted according to the type of CEPD. The risk of stroke was lower in the I&LCCA (filter cover the innominate and the left common carotid arteries) type CEPD group: RR 0.66, 95% CI 0.49–0.96, p = 0.03, I2 = 36%. However, there was no statistically significant difference in the risk of stroke in the TMCA [filter cover the three major cerebral arteries (innominate, left common carotid, and subclavian arteries)] type CEPD group: RR 0.81, 95% CI 0.36–1.80, p = 0.60, I2 = 0%. Conclusions In this meta-analysis, the I&LCCA-type CEPD can reduce the risk of stroke within 30 days following TAVI, but the TMCA type cannot.